Chapter Studi italiani su Dante nel mondo slavo: alcune considerazioni - Siedina, Giovanna (Biblioteca di Studi di Filologia Moderna, 2022)
The aim of this article is to provide a review, albeit not exhaustive, of Italian studies on Dante in the Slavic world. Starting from 1921, and the important essays published in the journal "L'Europa orientale", the author shows how interest in the reception of Dante in the Slavic world has never decreased among Italian Slavists, as well as specialists on Italian literature in the Slavic countries. This volume is one of many illustrating this rich history. In the second part of the essay, the author discusses the different contributions gathered in this volume, highlighting the connections among different areas of the Slavic world within the field of the reception of Dante's oeuvre.